Occurrence and Public Health Importance of Ascaridoid Nematodes in Red Porgy, Pagrus pagrus (Perciformes: Sparidae) - Abd El-Ghany, Amany M.; Mahmoud, Abdallah F.A.; El-Atabany, Adel I.M.; Attia, Salwa M.A. (Journal of Advanced Veterinary Research, 2023)
Anisakid nematodes have been found in a variety of marine fishes worldwide and they are known to cause anisakiasis and allergic symptoms in human. One-hundred and five fish specimens of different sizes of red porgy (Pagrus pagrus) were collected randomly from Sharkia fish markets originating from the Gulf of Suez, Red Sea, Egypt and examined for the presence of ascaridoid nematodes. The overall prevalence of ascaridoids was 36.19% (38/105). Four morphotypes belonging to two genera of anisakid nematodes (Anisakis type I and Terranova type II larvae) as well as one genus of raphidascarid; Hysterothylacium (larvae and adult) were reported during this study. Hysterothylacium larvae were the most predominant species (23.81%) and abundance value =1.68. Interestingly, Pagrus pagrus was found as new host and locality records for larvae of Terranova type II. The results revealed a significant statistical correlation between fish length and number of the recovered ascaridoid nematodes (rs= 0.244, P < 0.05). There was a positive correlation between the host length and presence of Anisakis type I L3 (rs=0.276, P < 0.001). Significant differences were observed between the occurrence of Terranova type II L3 and Hysterothylacium L3 occurrence (rs= 0.388, P < 0.001) and adult (rs= 0.442, P < 0.001). In addition, a highly significant relationship was observed between the presence of Hysterothylacium L3 and adult (rs= 0.428, P < 0.001). Furthermore, the obtained results were lower than the recommended Egyptian standards (Ë‚100 parasites/fish), demonstrating that human health risk through consumption of fish flesh is not possible.